Mid-term Results of Chimney and Periscope Grafts in Supra-aortic Branches in High Risk Patients. (September 2017) - Pecoraro, F.; Lachat, M.; Cayne, N.S.; Pakeliani, D.; Rancic, Z.; Puippe, G.; Criado, F.J.; Pfammatter, T.; Veith, F.J.; Krüger, B.; Neff, T.A.
Abstract : Purpose: Report mid-term outcomes of thoracic endovascular aneurysm repair (TEVAR) with chimney and periscope grafts (CPG) in supra-aortic branches (SAB). Methods: Retrospective analysis, from October 2009 to May 2014, of patients with aneurysms requiring TEVAR with zone 0/1/2 proximal landing in association with at least one CPG in the SAB. All patients were considered at high risk for conventional surgery. Peri-operative mortality and morbidity, retrograde type A dissection, maximum aortic transverse diameter (TD) and its post-operative evolution, endoleak, survival, freedom from cardiovascular re-interventions, and CPG freedom from occlusion during the follow-up were analysed. Results: Forty-one patients (28.05% EuroScore II) with thoraco-abdominal aortic aneurysm (17%), arch aneurysm (39%), descending aneurysm (34%), and aneurysm extending from the arch to the visceral aorta (10%) were included. Fifteen (37%) patients were treated non-electively. Fifty-nine SABs were treated with the CPG technique: one, two, three, and four CPG were employed in 71%, 19%, 5%, and 5% of patients, respectively. The proximal landing was in zone 0 in 49% of patients, zone 1 in 17%, and zone 2 in 34%. Technical success was 95%. Peri-operative complications and neurological events were registered in six (14.6%) patients and there were 5 deaths (12%). At a median follow-up of 21.2 (mean 22, SD 18; range 0–65) months, type I/III endoleaks were registered in three (7%) cases and re-intervention in six (15%) patients. A significant aneurysm sac shrinkage ( p <.001) was reported at mean follow-up and no significant aneurysm sac increase (>5 mm). The estimated 2 year survival, freedom from re-intervention, freedom from endoleak, and freedom from branch occlusion were 75%, 77%, 86%, and 96%, respectively. Conclusion: The chimney and periscope grafts technique was shown to be safe in aortic aneurysm disease involving the supra aortic branches, even in an emergency setting using off the shelf devices. Mid-term follow-up results in this high risk population are good, but longer follow-up is mandatory before this technique is used in intermediate-risk patients.